AB0531 Nutritional Status in Hospitalized Patients with Systemic Lupus Erythematosus. (10th June 2014) - Gonzalez-Noriega, M.; Atisha-Fregoso, Y.; Romero-Diaz, J.; Jakez-Ocampo, J.; Carrillo-Maravilla, E.; Rossiere, N.; Llorente, L.; Damasco-Avila, E.
Abstract : Background: Patients with systemic lupus erythematosus (SLE) may have an abnormal nutritional status, with alterations ranging from changes in body weight and composition associated with chronic glucocorticoid intake to a wasting syndrome associated with disease activity. Currently there is limited information on anthropometric characteristics and nutritional assessment of patients with SLE and the impact of malnutrition in these patients. Objectives: This is an exploratory study. The objective was to perform anthropometric and nutritional assessment of hospitalized patients with SLE and to identify any association between these measures and length of hospital stay. Methods: Patients with diagnosis of SLE who met the 2012 ACR/SLICC criteria, hospitalized in a single center between August 15, 2013 and January 15, 2014 were included. At hospitalization all patients were evaluated by a nutritionist, who collected anthropometric data, and calculate nutritional risk scores (Subjective Global Assessment (SGA) and nutritional risk index (NRI)), and by a rheumatologist who recorded the disease activity (SLEDAI 2K) and obtained the clinical data. The main outcome was duration of hospitalization, defined as the time until discharge or death. Results: Twenty eight patients (24 women, 85.7%), with a mean age of 33.75±15.3 years were included. The time from diagnosis of SLE to the hospitalization was 12.21±10.9 years; according to SLEDAI (cutoff>6) 11 patients had active disease at the time of assessment. Mean of hospital stay was 9 days (min 2, max 33), none of the patients died during follow-up. Considering body mass index, 2 patients (7.1%) were underweight, 17 (78.6%) eutrophic, 6 (21.4%) overweight and 3 (10.7%) were obese. Fourteen patients (50%) had A in the SGA, 6 (21.4%) had B and 8 (28.6%) C. According to the NRI values, we defined four grades of nutrition-related risk: i) major risk (NRI<83.5); ii) moderate risk (NRI 83.5–97.5); iii) mild risk (NRI 97.5–100); iv) No risk (NRI >100). Nine patients (32.1%) were classified as no risk, 3 (10.7%) as mild risk, 6 (21.4%) as moderate risk, and 10 (35.7%) as major risk. None of the parameters had statistically significant correlation with the duration of hospital stay, however, when patients were classified according to the NRI in two groups (major and moderate risk vs mild and no risk) a longer stay among which were considered at higher risk was found, with a median length of hospital stay of 9 days (IQR 6.25-12.25) vs 5.5 days (IQR 2.75-8.5), p=0.036. Conclusions: This study provides useful data about the characteristics of hospitalized patients with SLE. The nutritional risk index is outlined as a useful tool for the evaluation of these patients. We are currently conducting a follow-up study with a larger sample size to confirm the findings observed. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6039